Microsoft Windows XP plain & simple - Joyce, Jerry, 1950- (Microsoft Press, 2005)
Jump in wherever you need answers. Easy numbered steps show exactly what to do for the simplest ways to get the job done. Handy tips teach new techniques and shortcuts.